(untitled) (Revista Brasileira de História das Religiões, 2020)
There is increasing attention to religion and democracy in scholarly research in Brazil. In general terms, when scholars look to religion and democracy, an increasing number focus on the question of evangelicals and electoral politics. Research is reacting to the Brazilian political context provided by the most recent Presidential campaign and the inauguration of a ‘terribly evangelical’ President. This article considers religion and democracy, particularly with regard to laicité imported from France to Brazil, and indeed Latin America more widely. The article concludes with ‘Field Notes’ from interviews and conversations with Pentecostals about contemporary politics in Brazil.